2020
DOI: 10.1038/s41388-020-01560-0
|View full text |Cite
|
Sign up to set email alerts
|

Insights from transgenic mouse models of PyMT-induced breast cancer: recapitulating human breast cancer progression in vivo

Abstract: Breast cancer is associated with the second highest cancer-associated deaths worldwide. Therefore, understanding the key events that determine breast cancer progression, modulation of the tumor-microenvironment and metastasis, which is the main cause of cancer-associated death, are of great importance. The mammary specific polyomavirus middle T antigen overexpression mouse model (MMTV-PyMT), first published in 1992, is the most commonly used genetically engineered mouse model (GEMM) for cancer research. Mammar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 114 publications
7
91
0
Order By: Relevance
“…MMTV-PyMT crossed with cathepsin B knockout mice showed a delay in tumor onset and decreased metastasis compared to the WT mice [ 59 ]. Additionally, several studies have shown that PYMT tumor cells produce various immunosuppressive and chemiotactic molecules that modulate the tumor microenvironment and suppress the anti-cancer immune response to promote metastasis [ 60 ]. Ablation of STAT3 in the tumor epithelia of an inducible PyMT mouse model significantly increased immune cell infiltration in the primary tumor followed by tumor regression and absence of metastasis, suggesting that an immunosuppressive tumor microenvironment promoted by STAT3 is involved in modulating early tumor outgrowth and later metastasis [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…MMTV-PyMT crossed with cathepsin B knockout mice showed a delay in tumor onset and decreased metastasis compared to the WT mice [ 59 ]. Additionally, several studies have shown that PYMT tumor cells produce various immunosuppressive and chemiotactic molecules that modulate the tumor microenvironment and suppress the anti-cancer immune response to promote metastasis [ 60 ]. Ablation of STAT3 in the tumor epithelia of an inducible PyMT mouse model significantly increased immune cell infiltration in the primary tumor followed by tumor regression and absence of metastasis, suggesting that an immunosuppressive tumor microenvironment promoted by STAT3 is involved in modulating early tumor outgrowth and later metastasis [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MMTV-PyMT (polyomavirus middle T antigen) mouse model was applied for the widely accepted reason that it can mimic several aspects of human breast cancer, including initiation, histological and molecular progression, metastasis, and immunotherapies. Despite not being a human oncogene, PyMT imitates the signaling of receptor tyrosine kinases, which are commonly activated in human breast cancer 33 .…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the broadly used MMTV-PyMT mouse model that expresses polyoma middle T (PyMT) oncogenic protein in the mammary epithelium recapitulates some aspects of ERα-positive breast cancers. This model rapidly develops spontaneous luminal-like ERα-positive premalignant mammary lesions, sensitive to tamoxifen, which further progress to ERα-negative mammary carcinoma forming lung metastases [281,282]. In MMTV-PyMT females, ERα signaling favors tumor onset, tumor growth and pulmonary metastasis [282].…”
Section: Models Of Erα-positive Breast Cancersmentioning
confidence: 99%
“…This model rapidly develops spontaneous luminal-like ERα-positive premalignant mammary lesions, sensitive to tamoxifen, which further progress to ERα-negative mammary carcinoma forming lung metastases [281,282]. In MMTV-PyMT females, ERα signaling favors tumor onset, tumor growth and pulmonary metastasis [282]. Loss of TET2 that profoundly alters ERα signaling and mammary development was recently found to promote the growth of invasive MMTV-PyMT tumors and confer resistance to tamoxifen in vivo [226].…”
Section: Models Of Erα-positive Breast Cancersmentioning
confidence: 99%